2018
DOI: 10.1021/acs.cgd.8b01111
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Solubility of the Carbamazepine–Saccharin Cocrystal: A Charge Density Study

Abstract: Carbamazepine (CBZ) is used in the treatment of multiple neurological conditions. Although efficacious, its potential has been limited by its poor solubility, which means that patients are required to take very large doses to gain the desired effect. Co-crystals have been proposed as a means of improving the physicochemical properties of pharmaceutical compounds while maintaining their efficacy. CBZ cocrystallized with saccharin (SAC) and nicotinamide (NIC) have previously been studied, with the CBZ-SAC crysta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 61 publications
0
6
0
Order By: Relevance
“…The lower (the more negative) the value, the more stable and usually less soluble the crystal of a given compound, due to the greater amount of energy needed to break the interactions, although the dissociation process also releases some energy. 68…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The lower (the more negative) the value, the more stable and usually less soluble the crystal of a given compound, due to the greater amount of energy needed to break the interactions, although the dissociation process also releases some energy. 68…”
Section: Resultsmentioning
confidence: 99%
“…The lower (the more negative) the value, the more stable and usually less soluble the crystal of a given compound, due to the greater amount of energy needed to break the interactions, although the dissociation process also releases some energy. 68 During the characterisation of the final chalcogenadiazolecarboxylic acids we observed that 3 Se clearly differs in its physical properties from the other compounds. It has a much higher melting point (286-287 °C), which is relatively rare for an organic compound with such a low molecular weight, and additionally it has markedly reduced solubility in common organic solvents.…”
Section: Crystal Lattice Energiesmentioning
confidence: 91%
“…In order to fundamentally understand the driving force behind the formation of the cocrystals, especially the electronic properties of the atoms involved in weak interactions, 31 the molecular electrostatic potential of DMCAT and the two co-formers were calculated and visualized by Multiwfn and VMD software, as shown in Fig. S3 †.…”
Section: Resultsmentioning
confidence: 99%
“…This is mainly due to the reason that co-crystals usually do not diffract to very high resolutions. There are few reports in the literature on the electron density analysis of co-crystals, such as nicotinamide-salicylic acid and oxalic acid, 36 melamine–barbital co-crystal, 37 piroxicam–saccharin co-crystal, 38 carbamazepine–saccharin co-crystal, 39 carbamazepine–aspirin co-crystal, 40 NAPY, 26 antipyrene-2,4 dihydroxy benzoic acid, 41 which highlight the significance of electron-density-based topological analysis in the co-crystal assembly. Highly diffracting co-crystals of NAGA allow a thorough multipolar modeling of the electron density to derive electrostatic properties.…”
Section: Introductionmentioning
confidence: 99%